Pengaruh Return On Assets, Leverage, Corporate Governance, Ukuran Perusahaan, Dan Kompensasi Rugi Fiskal Terhadap Tax Avoidance (Studi Empiris Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Arif F, Fajar; , Eny Kusumawati, SE, MM, Ak (2017)
This research studied the impact of financial statement indicator to tax avoidance. ROA, Leverage, Corporate governance, Company Size, and Fiscal Lost Compensation were used as an independen variable which were assumed have an impact to tax avoidance (Dependen Variable) proxietd by Cash Effective Tax Rate (CETR). This research use purposive sampling criteria and double linear regression analysis test. The result was ROA, Leverage, Corporate governance, Company Size, and Fiscal Lost Compensation hade a simultanous significant impact to tax avoidance in companies listed in BEI 2012-2015 period. Corporate Governance, Company Size, Fiscal Lost Compensation influence tax avoidance partially and significantly. ROA and Leverage had no partial significant influence to tax avoidance. This result was consistent to previous research of Kurniasih and Sari (2013).